Radiographic assessment of the percutaneous Bianchi system technique for treatment of hallux valgus - Silva, Tércio Manoel de Vasconcelos; Moreno, Marcus Vinicius Mota Garcia; Guimarães, Janice de Souza; Marçal, Túlio Eduardo Vieira; Faleiro, Thiago Batista; Torres Gomes, Marilton Jorge; Risi, Michele (Journal of the Foot & Ankle, 2021)
Objective: To present initial radiographic results of surgical correction of the hallux valgus angle (HVA) and the intermetatarsal angle (IMA) using the percutaneous Bianchi system (PBS) technique. Methods: Seventeen patients with moderate to severe hallux valgus (HV) were exclusively treated with the PBS technique and assessed radiographically preoperatively and during the postoperative period, from January 2019 to January 2020. The degree of deformity correction was recorded, based on the HVA and the IMA. Stata (v. 14.0) software was used for statistical analyses. Pre-surgical and post-surgical mean HVA and IMA were compared using Student’s t test for paired samples and the McNemar test was used to compare HVA and IMA categories. Statistical significance was set at 5% and 95% confidence intervals were estimated. Results: Both HVA and IMA were reduced significantly during the assessment period. Mean radiographic correction of the HVA was 15.1° and mean radiographic correction of the IMA was 7.3. Conclusions: According to the results presented, use of the PBS technique achieved adequate correction of the radiographic parameters of the patients who underwent the treatment as proposed, although it is necessary to conduct additional studies with longer follow-up to achieve a higher recommendation level. Level of Evidence IV; Therapeutic Studies; Case Series.